Emergent Triple-Branched TEVAR and Redistribution of the Branches to the Supra-Aortic Target Vessels for Treatment of a Contained Ruptured Descending Aortic Aneurysm Associated With a Chronic Type A Aortic Dissection. (April 2021) - Stana, Jan; Fernandes Prendes, Carlota; Banafsche, Ramin; Konstantinou, Nikolaos; Rantner, Barbara; Pichlmaier, Maximilian; Tsilimparis, Nikolaos
Purpose: To demonstrate the feasibility of urgent endovascular treatment of a chronic type A dissection and contained rupture of the false lumen using a noncustomized triple-branched arch endograft, which necessitated reassignment of the branches to the supra-aortic vessels. Case Report: A 57-year-old patient with a contained rupture of the descending thoracic aorta, in the setting of a chronic type A dissection and a maximum aortic diameter of 85 mm, was converted to endovascular repair after failure of an open surgical approach. A custom-made triple-branched arch endograft designed for another patient was employed, with concomitant occlusion of the false lumen using a Candy Plug occluder. To adjust the graft's configuration to the patient's anatomy, the supra-aortic vessels were not assigned to the originally planned branches. The 12-month follow-up angiography demonstrated a satisfactory result. Conclusion: A noncustomized triple-branched arch endograft can be used in an emergency setting to treat chronic type A dissection, reassigning the branches to the supra-aortic vessels as needed.